2019
DOI: 10.1097/olq.0000000000000979
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Persistence, Clearance, and Correlates of Genital Human Papillomavirus Infection and Anogenital Warts in a Cohort of Men Living With Human Immunodeficiency Virus in South Africa

Abstract: A cohort study of human immunodeficiency virus–positive men in Johannesburg, South Africa found that they have high persistence of genital human papillomavirus infection and anogenital warts. A combination of early and effective use of antiretroviral therapy and human papillomavirus vaccination could reduce this burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…The incidence rate of anal HPV infection was 16.0 cases/ 100 person-years among those without HPV at baseline, and was 26.8 cases/100 person-years for getting any new HPV genotype among all participants, showing that HPV incidence was high in men with HIV. The incidence rate in our study was similar to a cohort study in America (21.3 cases/100 person-years) [14], higher than a South African study (2.9 cases/100 person-years) [15], and lower than a South-East Asian study (34.1 cases/100 person-years) [8]. We also found that the incidence rate among HIV-positive homosexual men in this study was lower than that of MSM in Guangdong, China (29.6 vs. 37.6 cases/100 person-years) [16], which had a younger study population.…”
Section: Discussionsupporting
confidence: 87%
“…The incidence rate of anal HPV infection was 16.0 cases/ 100 person-years among those without HPV at baseline, and was 26.8 cases/100 person-years for getting any new HPV genotype among all participants, showing that HPV incidence was high in men with HIV. The incidence rate in our study was similar to a cohort study in America (21.3 cases/100 person-years) [14], higher than a South African study (2.9 cases/100 person-years) [15], and lower than a South-East Asian study (34.1 cases/100 person-years) [8]. We also found that the incidence rate among HIV-positive homosexual men in this study was lower than that of MSM in Guangdong, China (29.6 vs. 37.6 cases/100 person-years) [16], which had a younger study population.…”
Section: Discussionsupporting
confidence: 87%
“…The appearance of CW is, therefore, the result of viral multiplication persistence but remains transient until 1–2 dozen months ( 34 , 36 , 39 ). This viral persistence rate and therefore the relative risk of CW occurrence is proportional to age [66% in children and 92% in adults ( 40 )], as children are either not exposed or are less exposed than adults to viral persistence risks, including any sexual practices, smoking, use of hormonal contraceptives, and other infections ( 41 44 ).…”
Section: Epidemiology Of Hpv Infection and Related Diseasesmentioning
confidence: 99%
“…Regionally, SSA appears to have slightly higher AGW incidence and prevalence rates ( 60 ), especially among people with multi-sexual partners and those who are immunocompromised ( 41 44 ). In developed regions, the incidence of AGW incidence appears low (around 1.5% in the USA) and seems to decrease because of vaccine implementation ( 49 ).…”
Section: Epidemiology Of Hpv Infection and Related Diseasesmentioning
confidence: 99%
“…To our knowledge, there are no other data on the effect of mental health parameters on response to AGW treatment. As far as other parameters are concerned, AGW clearance has been associated with high vs low CD4+ count in men living with human immunodeficiency virus, 25 while increased recurrence rates of AGW have been associated with smoking. 26 Cryotherapy is one of the most commonly used provideradministered treatments for AGW because it is simple, inexpensive and safe.…”
Section: Discussionmentioning
confidence: 99%